Gold Mining Conflict Between the Community and the Government in Nagari Simpang Tonang, Dua Koto District, Pasaman Regency. - Ifti Syariah; Endrizal; Yetty Oktayanti (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This paper is entitled "Gold Mining Conflict Between the Community and the Government in Nagari Simpang Tonang, Dua Koto District, Pasaman Regency". The purpose of this research is to describe what is behind the conflict and the form of conflict that occurs. The theory used in this research is Dahrendorf's social conflict theory. Then the method used is qualitative method from Maleong with data collection techniques of observation, interview and documentation. The results of this study are related to regional autonomy which is the obligation or authority of autonomous regions to regulate and manage their own government affairs and the interests of the community, one of which is to manage and manage the results of natural resources and natural potential to improve the community's economy. Conflict over the authority issued by the government to the community related to the management of natural resources and natural potential occurs. The background of the conflict is that there is no permission from community leaders, not in accordance with the permits obtained with the mined area, environmental pollution, economic decline, socio-cultural damage. This form of conflict is also destructive, which will lead to violence